2015
DOI: 10.1186/s12889-015-1513-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of family and friend smoking on intentions to smoke and smoking-related attitudes and refusal self-efficacy among 9–10 year old children from deprived neighbourhoods: a cross-sectional study

Abstract: BackgroundSmoking often starts in early adolescence and addiction can occur rapidly. For effective smoking prevention there is a need to identify at risk groups of preadolescent children and whether gender-specific intervention components are necessary. This study aimed to examine associations between mother, father, sibling and friend smoking and cognitive vulnerability to smoking among preadolescent children living in deprived neighbourhoods.MethodsCross-sectional data was collected from 9–10 year old childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 47 publications
6
36
3
3
Order By: Relevance
“…Due to the cross‐sectional nature of this study, it is unclear if these factors led to differences observed in cigarette smoking in this study. However, these factors have been shown to be important contributors to adolescent smoking in previous studies . The differences found in this study indicate that focusing or including parents and adults in nonmetro communities in tobacco‐related interventions may be important.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Due to the cross‐sectional nature of this study, it is unclear if these factors led to differences observed in cigarette smoking in this study. However, these factors have been shown to be important contributors to adolescent smoking in previous studies . The differences found in this study indicate that focusing or including parents and adults in nonmetro communities in tobacco‐related interventions may be important.…”
Section: Discussioncontrasting
confidence: 59%
“…However, these factors have been shown to be important contributors to adolescent smoking in previous studies. 25,26 The differences found in this study indicate that focusing or including parents and adults in nonmetro communities in tobacco-related interventions may be important. Encouraging nonmetro parents to adopt a home smoking ban may be particularly beneficial.…”
Section: Discussionmentioning
confidence: 85%
“…If no parent smoked and an older sibling smoked, the OR that the 12th grader would smoke was 1.85 compared to 1.49 if a parent smoked [21]. Intentions to smoke and smoking-related attitudes were influenced by family and friend smoking status [22] and family structure affected the adolescents smoking stages [23]. These findings demonstrate that family smoking is a crucial factor that affects adolescent smoking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Niat yang tinggi mempengaruhi orang tersebut untuk melakukan perilaku yaitu perilaku pencegahan konsumsi alkohol dan merokok. Hal ini juga didukung oleh penelitian Mcgee at al (2015), dimana tidak terdapat pengaruh langsung sikap terhadap perilaku pencegahan merokok, namun sikap dapat melalui niat dalam mempengaruhi perilaku pencegahan merokok pada individu (Mcgee et al, 2015). Sikap juga merupakan faktor yang signifikan dalam memprediksi niat untuk melakukan perilaku seperti merokok (Karimy et al, 2015).…”
Section: Pembahasanunclassified